Negotiating Boundaries: Lived Experiences of Work-Life Balance among Hybrid Workers in the Digital Age - Hasan Setyo Nugroho (Prodi Sosiologi FISIP Universitas Teuku Umar, 2025)
The transformation of work systems towards a hybrid model has fundamentally changed the psychological dynamics of balancing professional demands and personal life in the digital age, especially in urban communities. This study explores how eight hybrid workers negotiate the boundaries between work and personal space, build emotional balance, and shape their professional identity amid digital flexibility and pressure. Using an interpretive phenomenological qualitative approach, informants from the education, technology, and public administration sectors in Yogyakarta were interviewed in depth to uncover the subjective meaning of their daily experiences. Reflective thematic analysis reveals three main contexts: the separation of work and personal spheres is now psychological in nature; adaptive strategies such as self-regulation and emotional resilience overcome digital fatigue; and the formation of professional identity is performative through dynamic digital interactions. These findings expand the literature on work-life interface and psychological work identity with a non-Western perspective, emphasizing the role of culture, digital autonomy, and emotional support in maintaining psychological well-being. Practically, this research highlights the need for adaptive and psychologically balanced organizational policies, affirming that work-life balance in the hybrid era is a continuous negotiation process between space, time, and the evolving meaning of self.